Sex, Identity, Aesthetics The Work of Tobin Siebers and Disability Studies - Kim, Jina B.; Kupetz, Joshua; Lie, Crystal Yin; Cynthia, Wu (University of Michigan Press, 2021)
The late Tobin Siebers was a pioneer of, and one of the most prominent thinkers in, the field of disability studies. His scholarship on sexual and intimate affiliations, the connections between structural location and coalitional politics, and the creative arts has shaped disability studies and continues to be widely cited. Sex, Identity, Aesthetics: The Work of Tobin Siebers and Disability Studies uses Siebers' work as a launchpad for thinking about contemporary disability studies. The editors provide an overview of Siebers' research to show how it has contributed to humanistic understandings of ability and disability along three key axes: sex, identity, and aesthetics. The first section of the book explores how disability provides a way for scholars to theorize a wider range of intimacies and relationalities, arguing that disabled people seek sexual access and revolution in ways that transgress heteronormative dictates on sexual propriety. The second part of the book works outward from Siebers' work to looks at how disability broadens our concepts of social location and political affiliations. The final section examines how disability challenges traditional notions of artistic beauty and agency. Rather than being a strictly commemorative collection meant to mark the end of a major scholar's career, this collection shows how Siebers' foundational work in disability studies remains central to and continues to inspire scholars in the field today.